Pedagogical contributions of Arnold Schönberg composition's method - Josep Gustems Carnicer; Magda Polo Pujadas (Ediciones Complutense, 2017)
Arnold Schoenberg's twelve-tone technique made him one of the most influential composers of the twentieth century, but his contribution to music pedagogy remains far less well known. This article is a descriptive and interpretive work and therefore tries to present the main ideas of Schönberg, from theoretical references. This paper explores Schoenberg's concepts about music education as they emerge in the collection of essays published under the title Style and Idea: the dialectic between tradition and modernity; the social dimensions of music education; the notion of musicality; the presence of emotion in twelve-tone composition; and the composer's conviction that contemporary creation could be an axis of music education. This research also argues that Schoenberg's ideas about music education make him deserving of greater attention amongst music teachers and pedagogues today.